Experimental study of liquid immiscibility in the Kiruna-type Vergenoeg iron–fluorine deposit, South Africa - Hou, Tong; Charlier, Bernard; Namur, Olivier; Schütte, Philip; Schwarz-Schampera, Ulrich; Zhang, Zhaochong; Holtz, Francois (Amsterdam : Elsevier, 2017)
In this study we experimentally assess whether the bulk composition of the Kiruna-type iron–fluorine Vergenoeg deposit, South Africa (17 wt.% SiO2 and 55 wt.% FeOtot) could correspond to an immiscible Fe-rich melt paired with its host rhyolite. Synthetic powder of the host rhyolite was mixed with mafic end-members (ore rocks) in variable proportions. Experimental conditions were 1–2 kbar and 1010 C, with a range of H2O and F contents in the starting compositions. Pairs of distinct immiscible liquids occur in experiments saturated with fluorite, under relatively dry conditions, and at oxygen fugacity conditions corresponding to FMQ 1.4 to FMQ+1.8 (FMQ = fayalite-magnetite-quartz solid buffer). The Si-rich immiscible liquids contain 60.9–73.0 wt.% SiO2, 9.1–12.5 wt.% FeOtot, 2.4–4.2 wt.% F, and are enriched in Na2O, K2O and Al2O3. The paired Fe-rich immiscible melts have 41.0–49.5 wt.% SiO2, 20.6–36.1 wt.% FeOtot and 4.5–6.0 wt.% F, and are enriched in MgO, CaO and TiO2. Immiscibility does not develop in experiments performed under water-rich (aH2O > 0.2; a = activity) and/or oxidized (>FMQ+1.8) conditions. In all experiments, solid phases are magnetite, ±fayalite, fluorite and tridymite. Our results indicate that the rocks from the Vergenoeg pipe crystallized in a magma chamber hosting two immiscible silicate melts. Crystallization of the pipe from the Fe-rich melt explains its extreme enrichment in Ca, F and Fe compared to the host rhyolitic rocks. However, its low bulk silica content compared to experimental Fe-rich melts indicates that the pipe formed by remobilization of a mafic crystal mush dominated by magnetite and fayalite. Segregation of evolved residual liquids as well as the conjugate immiscible Si-rich melt produced the host rhyolite. The huge amount of fluorine in Vergenoeg ores ( 12 wt.% F) can hardly be explained by simple crystallization of fluorite from the Fe-rich silicate melt (up to 6 wt.% F at fluorite saturation). Instead, we confirm a previous hypothesis that the fluorite enrichment ...